SEDEKAH DALAM PERSFEKTIF AL-QURAN (Suatu Tinjauan Tafsir Maudhu’i) - Drs. H Firdaus (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
Alms may difinisikan as a gift given by a Muslim to another person spontaneously and voluntarily without being limited by time and a certain amount and it was done as a form of implementation of the recognition and proof of the truth of one's faith with the hope rida nd reward from Allah alone. Alms is interpreted zakat can function in addition to being an alternative when the obligation or instigation of religion is not yet implemented or get hitch can also maintain and freeing of one's possessions out of habit, especially for those who issued their zakat, because in essence charity is able to clean up their property and keeping well out of things that can be detrimental. While the group is entitled to receive alms (sadaqah) according to the Qur'an is (1) Those indigent (2) The poor, (3) Board-administrators zakat, (4) The mu'allaf who persuaded him, for (freeing) slaves, (5) those who owe, to the way of God (6) people who walk, to the way of Allah and (7) people who are in overseas.